Isolation of Phosphate Solubilizing Endophytic Fungi From Rice Plant Root - Dezi Handayani; Mades Fifendy; Verawati Yesni (Bioscience, 2018)
Root endophytic fungi plays different roles for plant, such as plant growth promoting properties, agents to control phytopathogens, and increase phosphorus uptake. Since phosphorus are essential for plant growth and its occurance are limited, so it is necessary to explore these fungus to replace the used of synthetic fertilizer. The objective of this study were to obtain root endophytic fungi from rice plant and to determine its phosphate solubilization ability. The root organ of rice plant was subjected for isolation. Pikovskaya medium was use to determine the fungal phosphorus solubilization ability. Fungal morphological characteristics was carried out by macroscopic and microscopic appearance assessment using microscope. Seven endophytic fungi were successfully isolated from rice plant root sample. Four isolate were micelial steril with no conidia, two isolate refers to Aspergillus and 1 isolate have 2-4 conidia at the tip of conidiophores. Amongs 7 endophytics fungi, only one isolate (P2B3) had the ability to solubilize phosphate with the phosphate solubilization index value 20.45 %.